The diagnostic value of TTF1, P63, HMWK [34βE12], CK7, and CD56 immunostaining in classification of lung carcinoma - Amir Hossein Jafarian; Masoumeh Gharib; Nema Mohammadian Roshan; Samaneh Sherafatnia; Abbas Ali Omidi; Sahar Bagheri (Iranian Society of Pathology, 2017)
Background & objective: The histologic distinction of small cell from non-small cell lung carcinoma and correct identification of all subtypes of lung carcinoma are very important in treatment management. The main method for histologic classification of lung tumors is based on morphology. However, in small bronchoscopic biopsies in particular, distinction is very difficult upon morphology alone. The current study aimed at evaluating the utility of a panel of antibodies, consisting of thyroid transcription factor (TTF-1), P63, high molecular weight keratin [HMWK (34βE12)], cytokeratin (CK7), and cluster of differentiation (CD56) for accurate distinction of bronchogenic carcinomas. Methods: Bronchoscopic biopsies of 60 lung carcinoma cases including 20 small cell carcinomas, 20 adenocarcinomas, and 20 squamous cell carcinomas (SCCs) with typical morphologic features were selected. All these cases were immunohistochemically stained for TTF-1, P63, HMWK (34βE12), CK7, and CD56. All immunostained slides were scored as either positive or negative. Results: The mean age of the patients was 60 years; ranged from 35 to 81. Sixteen patients were female and 44 were male. All adenocarcinomas were positive for CK7 and most of them (18/20; 90%) were positive for TTF-1. Most of small cell lung carcinomas were positive for TTF-1 (17/20; 85%), and CD56 (18/20; 90%). All squamous cell carcinomas (SCCs) were negative for TTF-1, but most of them were positive for HMWK (34βE12) and P63. Conclusion: The obtained data showed that TTF-1, P63, CK7, CD56 and/or 34βE12 represent a useful panel of antibodies to identify lung carcinoma subtypes in small bronchoscopic biopsies.